Randomized trial of micafungin versus fluconazole as prophylaxis against invasive fungal infections in hematopoietic stem cell transplant recipients. Issue 5 (November 2016) - Park, Silvia; Kim, Kihyun; Jang, Jun Ho; Kim, Seok Jin; Kim, Won Seog; Chung, Doo Ryeon; Kang, Cheol-In; Peck, Kyong Ran; Jung, Chul Won
Summary: Objectives: Invasive fungal infections (IFIs) cause significant morbidity and mortality among recipients of hematopoietic stem cell transplantation (HSCT). Although fluconazole is used widely as an antifungal prophylactic agent in these patients, it is not reliably effective against mold infection including invasive aspergillosis. Micafungin provides antifungal activity against Candida and Aspergillus species, and previous studies have demonstrated its efficacy when used as a prophylactic agent for fungal infection in neutropenic patients. Here, we evaluated and compared the incidence of proven or probable IFIs after antifungal prophylaxis using micafungin or fluconazole. Methods: This was a prospective, single-center, phase II study involving adult patients who received allogeneic or autologous HSCT. Patients were randomly assigned to micafungin or fluconazole arms in a ratio of 2:1, and the treatment was initiated within 24 h of HSCT and maintained for up to 21 days. The primary end point was the incidence of proven or probable IFIs during the 100 days after HSCT. The secondary end points were the incidence rates of possible, proven, or probable IFIs, need to change the antifungal agent before engraftment, IFI-related mortality, and survival within 100 days after transplantation. Results: Between March 2010 and May 2015, a total of 257 patients were enrolled. After exclusion of seven patients who did not receive at least one dose of a study treatment, 250 patients (micafungin, n = 165; fluconazole, n = 85) were included in the analysis of clinical efficacy. The median age was 47 years (range, 20–64). Allogeneic and autologous transplantations were performed in 56.0% (n = 140) and 44.0% (n = 110) of the patients, respectively. Baseline characteristics were well balanced between the two groups. Overall, the incidence of proven and probable IFIs within 100 days of HSCT was 7.6% (n = 19). The percentages of patients who experienced proven or probable IFIs did not differ significantly between the micafungin and fluconazole groups: 7.3% and 8.2%, respectively (p = 0.786). Thirteen patients in the micafungin arm (7.9%) and eight patients in the fluconazole arm (9.4%) needed a change in antifungal agent before engraftment (p = 0.824). Mortality within 100 days after HSCT did not differ significantly between groups: 9.1% vs 12.9% in the micafungin and fluconazole arms, respectively (p = 0.345). Conclusion: Micafungin is comparable to fluconazole for the prevention of IFIs in HSCT recipients.